2018
DOI: 10.1007/s11136-018-1991-4
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Alzheimer’s Disease Cooperative Study-Activities of Daily Living Inventory to the Health Utility Index Mark III

Abstract: The MRM is accurate at the group level. The regression-based mapping methods are more accurate for making individual-level prediction. In addition, CLAD also performed reasonably well at the group level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A study that compared the use of the dementia-specific QoL-AD and the general instrument HUI3 found that HUI3 results had a stronger correlation with other outcome measures, including functional abilities, cognition, dependence, and behavior, than the QoL-AD [ 56 ]. Other researchers have noted that while it is a general instrument, the HUI3 includes domains such as speech and cognition that are important for patients with dementia [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study that compared the use of the dementia-specific QoL-AD and the general instrument HUI3 found that HUI3 results had a stronger correlation with other outcome measures, including functional abilities, cognition, dependence, and behavior, than the QoL-AD [ 56 ]. Other researchers have noted that while it is a general instrument, the HUI3 includes domains such as speech and cognition that are important for patients with dementia [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are other regression-based methods, such as the Tobit regression and indirect mapping by multinomial logistic regression [7, 18]. These regression methods do not consistently perform better than the OLS [7, 17, 19].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that OLS mapping under-estimates variability and therefore inflates type 1 errors [5]. Furthermore, OLS mapping tends to under-estimate the health utility of people in good health states and over-estimate it among people in bad health states, which leads to under-estimates of the incremental cost-utility ratio [15, 1921].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations